Office system with audit history - MURDOCK; DAVID M (1995)
A system is disclosed for the automation of virtually all clerical functions in an office, such as for example, an insurance agency. Virtually any document generated by the office may be printed without the need for pre-printed forms, as the system prints such forms on a laser printer near the worker requesting the form, using a page description language (PDL) appropriate to the printer. The clerical activity involved in maintaining, updating, retrieving, displaying and printing information relating to the functions of the office is supported. A complete audit history of all activity to a specific database (DB) file record is maintained without saving the entire DB record in a historical file. The system also supports a worker when it is desired to interrupt a particular task and execute a different task, without losing information already entered for the first task, but without allowing the worker to exit the system without completing or accounting for the first task.